ESTUDIO DEL FITOPLANCTON DURANTE LAS PRIMERAS ETAPAS DE LLENADO DEL EMBALSE DE LA CENTRAL HIDROELECTRICA DE BETANIA, HUILA-COLOMBIA - Duque, Santiago; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
The present work evaluated the ñrst stages of succesion of the phytoplankton community persent in the "Central Hidroelectrica de Betania" during december of1986and april of1987, (ñrstmonthsñlling). Onehundred and one taxa were reported, sixteen of wich were not registred for Colombia. The geographic, physico-chemical and biologicaj characteristics allowed the oligotrophic as well as eutrophic phytoplankton species colonization. This species themselves to the hydrodinamic conditions that indicate layer stratiphication and difference between the two dams branches (Y aguará and Magdalena)